Evidence-based teaching interventions for emergent multilingual students in high school science classrooms: a literature review - Uma Ganesan (Discover Education)
Abstract As student populations in the United States grow increasingly linguistically and culturally diverse, asset-oriented pedagogical approaches become essential for leveraging the linguistic talents of multilingual students in science education. This literature review explores evidence-based instructional interventions supporting emergent multilingual learners in deeply engaging with scientific practices and communication in high school science classrooms. The review examined nine peer-reviewed studies published between 2012 and 2023, focusing on instructional strategies for multilingual learners in secondary science education. Findings reveal promising interventions such as the 5E instructional model, think-pair-share discussions, translanguaging techniques, and culturally responsive pedagogy. These approaches, grounded in sociocultural theory and systemic functional linguistics, conceive learning as a social process involving cultural tools like language to construct knowledge. The efficacy of these interventions relies on their adaptability to diverse student backgrounds, classroom dynamics, and teacher readiness. Emerging effective strategies encompass technology-enhanced learning for multilingual science students, interactive science notebooks, and integrating content and language instruction for emergent multilinguals. Further research is needed to refine these models for multilingual youth across diverse high school settings. Advancing scientific literacy and educational equity requires educators to embrace asset-oriented pedagogies that integrate content, language, and literacy development, drawing on established theories to cultivate robust disciplinary thinking and knowledge acquisition for all students.